THE INFLUENCE OF MEDICAL SERVICE QUALITY AND TRUST ON LOYALTY WITH PATIENT SATISFACTION AS AN INTERVENING VARIABLE IN THE INPATIENT WARD OF BHAYANGKARA HOSPITAL BANJARMASIN - Putriana Sitompul; Farida Yuliaty; Ayu Laili Rahmiyati; Kosasih; Vip Paramarta; Fitriana (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the influence of medical service quality and trust on patient loyalty with patient satisfaction as an intervening variable in the inpatient ward of Bhayangkara Hospital Banjarmasin. Hospitals are required to consistently provide comprehensive healthcare services, maintain patient trust, and enhance the quality of their services in order to improve patient satisfaction. This research employed a quantitative approach. The sample of this study consisted of 78 patients at Bhayangkara Hospital Banjarmasin. Data analysis was carried out using descriptive analysis and verification analysis with path analysis. The findings reveal that service quality and trust have a significant effect on improving patient satisfaction. Enhancements in service quality and trust can significantly contribute to higher levels of patient satisfaction. Service quality also has a significant effect on increasing patient loyalty, indicating that improved service quality can significantly foster greater patient loyalty. However, service quality and trust were found to have no direct significant effect on patient loyalty. Although improvements in service quality and trust may encourage higher patient loyalty, the effect was not statistically significant. Patient satisfaction demonstrated a significant influence on patient loyalty, suggesting that increased patient satisfaction can significantly enhance patient loyalty. Moreover, trust was shown to have a significant effect on patient loyalty when mediated by patient satisfaction. While improvements in trust may encourage greater loyalty through increased satisfaction, the effect was not statistically significant.